In situ Resource Utilization and Reconfiguration of Soils Into Construction Materials for the Additive Manufacturing of Buildings - Bajpayee, Aayushi; Farahbakhsh, Mehdi; Zakira, Umme; Pandey, Aditi; Ennab, Lena Abu; Rybkowski, Zofia; Dixit, Manish Kumar; Schwab, Paul Arthur; Kalantar, Negar; Birgisson, Bjorn; Banerjee, Sarbajit (Frontiers in Materials, 2020)
The construction industry is being buffeted by winds of change, balancing the urgent need to remedy deteriorating infrastructure in the developed world and the push to build new infrastructure in emerging economies whilst devising means to better its catastrophic carbon footprint. Much of the deleterious environmental impact of construction results from the utilization of concrete as well as inefficiencies across the construction process that result in considerable waste and energy expenditure. Additive manufacturing methods stand poised to substantially transform the industry by enhancing automation, enabling economy of materials use, and allowing for unprecedented fusion of form and function; however, reliance on concrete as the extrusive material of choice has the potential to greatly compound mounting environmental challenges. In this perspective, we discuss our efforts to develop an altogether new palette of naturally sourced construction materials based on natural soils, which are reconfigured into extrudable formulations compatible with additive manufacturing. We furthermore delineate a roadmap bringing together soil chemistry with composite science, modeling of mesoscale phenomena, rheological studies of extrudable soil “inks”, generative design, post-synthetic modification, and the development of robust structure—function correlations relating atomistic and mesoscale structures as well as geometry of the architectures to load-bearing capabilities and mechanical response. We illustrate this approach using a naturally harvested burlewash clay sample crosslinked through formation of a siloxane framework, which has been 3D printed into a load-bearing structure. The need for an integrated life cycle assessment approach is emphasized to ensure development of a new palette of sustainable construction materials.